1998
DOI: 10.1143/jjap.37.l278
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium Microwave Emission from DC-Biased High Tc YBa2Cu3O7-y Junctions

Abstract: Non-relativistic Compton profiles (in the impulse approximation) have been calculated for the He, Li, Be, B and Ne atoms from the numerical wavefunctions generated by four local density models for exchange correlation. Two of the models were simple P ' '~ schemes (p is the electron charge density): Xa,'l (the common form of the X a approximation) and X x / 2 ( X a with a stepfunction radial dependence for a). The other two, due to Hedin and Lundqvist and to Ng, contain p-dependent terms beyond the X r approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…When several branches were traced out, it appeared sequentially. These emissions are qualitatively different from conventional Josephson self-emission and are quite similar to those observed by tunnel injection of quasiparticles into YBCO, EBCO and BSCCO films given above [6][7][8] and are considered to be the incoherent plasmon emission arising from the electron-plasmon interaction. The emission of plasmons leads to microwave emission into free space.…”
Section: Low-voltage Injection Regimementioning
confidence: 59%
See 3 more Smart Citations
“…When several branches were traced out, it appeared sequentially. These emissions are qualitatively different from conventional Josephson self-emission and are quite similar to those observed by tunnel injection of quasiparticles into YBCO, EBCO and BSCCO films given above [6][7][8] and are considered to be the incoherent plasmon emission arising from the electron-plasmon interaction. The emission of plasmons leads to microwave emission into free space.…”
Section: Low-voltage Injection Regimementioning
confidence: 59%
“…The results for microwave emissions detected at 11.6-47 GHz were qualitatively similar among YBCO, EBCO and BSCCO samples. Figure 3 and 4 show typical results for the microwave emissions from quasiparticleinjected YBCO [6,7] and BSCCO [12] films, respectively, at the receiver frequency 47 GHz at different temperatures. At low temperatures (T = 4.2 K-10 K), the detected power increased almost linearly with increasing injection current, not being proportional to the injected power, suggesting the incoherent emission of microwaves.…”
Section: High-voltage Injection Regimementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been reported that when a high-T c superconductor/insulator/normal metal tunnel junction is biased at a finite current, broadband microwaves are emit-ted [7][8][9]. The observed phenomenon is quite different from the Josephson self-emission and has been considered as Josephson plasma emission.…”
Section: Introductionmentioning
confidence: 99%